2020
DOI: 10.21511/im.16(2).2020.11
|View full text |Cite
|
Sign up to set email alerts
|

The impact of motivation factors and intention to adopt Jordan as a destination for medical tourism in the Middle East

Abstract: The study aimed to investigate the impact of motivation factors on an individual’s decision to choose Jordan as their primary tourism destination in the Middle East. The decision to choose Jordan as a medical destination will be analyzed based on factors, including government support; push engagement, and image perception. To this end, the study will gather data from 300 online individuals who have traveled to the Middle East for medical purposes. A qualitative approach will be adopted to provide insight into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…In the context of remote learning, self-regulated learning has been found to increase intention to enroll in online courses in the near future ( Chen and Hwang, 2019 ). In addition, different studies suggested that students with low self-regulated learning skills are more likely to resist virtual courses than those with high self-regulated learning competencies ( Al-Adwan et al, 2018a , b ; Al-Adwan, 2020 ). Moreover, Al-Adwan (2020) found that the lower students’ self-regulation, the less they will recognize the value of the usefulness and functionality of virtual courses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of remote learning, self-regulated learning has been found to increase intention to enroll in online courses in the near future ( Chen and Hwang, 2019 ). In addition, different studies suggested that students with low self-regulated learning skills are more likely to resist virtual courses than those with high self-regulated learning competencies ( Al-Adwan et al, 2018a , b ; Al-Adwan, 2020 ). Moreover, Al-Adwan (2020) found that the lower students’ self-regulation, the less they will recognize the value of the usefulness and functionality of virtual courses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different studies suggested that students with low self-regulated learning skills are more likely to resist virtual courses than those with high self-regulated learning competencies ( Al-Adwan et al, 2018a , b ; Al-Adwan, 2020 ). Moreover, Al-Adwan (2020) found that the lower students’ self-regulation, the less they will recognize the value of the usefulness and functionality of virtual courses. Thus, students with a more self-regulated learning process can perform better and be more confident in dealing with the new technology involved in online courses ( Chen and Hwang, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ianya berfungsi kepada kecenderungan atau kesanggupan serta rintangan yang dihadapi bagi mengadakan perjalanan. Di sini kesanggupan dan kemampuan seseorang individu dipengaruhi oleh kehendaknya sendiri iaitu motivasi (Seo et al 2019;Al Adwan 2020;Zhang & Walsh 2021;Iványi & Bíró-Szigeti 2021), kedudukan sosio-ekonomi (Yeh & Liu 2019;Promsivapallop & Kannaovakun 2020;Gavurova et al 2020;Švec et al 2021;An & Alarcón 2021), keberkesanan pemasaran dan promosi (Chrząścik 2019;Castañeda et al 2020;Korbiel 2021;Tinakhat 2021;Yim et al 2021) yang dilakukan. Pemasaran dan promosi penting terutama bagi meningkatkan permintaan jangka panjang di samping memberi pendedahan kepada masyarakat umum.…”
Section: Pengenalanunclassified
“…Neferneferuaten Nefertiti, queen of the 18th Dynasty of Ancient Egypt, continues to influence perceptions of beauty, even today 2 . In the modern day, countries in the Middle East have rapidly growing beauty markets 3–6 . Within the region, Iran has among the highest rates of cosmetic procedures, and Dubai, often referred to as the plastic surgery hub of the Middle East, has the highest concentration of cosmetic surgeons in the world, with 47 cosmetic surgeons per 1 million people 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…2 In the modern day, countries in the Middle East have rapidly growing beauty markets. [3][4][5][6] Within the region, Iran has among the highest rates of cosmetic procedures, and Dubai, often referred to as the plastic surgery hub of the Middle East, has the highest concentration…”
mentioning
confidence: 99%